Restored intertidal eelgrass (Z. marina) supports benthic communities taxonomically and functionally similar to natural seagrasses in the Wadden Sea - Gräfnings, Max L. E.; Grimm, Ise; Valdez, Stephanie R.; Findji, India; van der Heide, Tjisse; Heusinkveld, Jannes H. T.; Meijer, Kasper J.; Eriksson, Britas Klemens; Smeele, Quirin; Govers, Laura L. (Frontiers in Marine Science, 2024)
Ecological restoration has become an important management-tool to counteract the widespread losses of seagrass meadows and their associated biodiversity. In the Dutch Wadden Sea, long-term restoration efforts have recently led to the successful restoration of annual eelgrass (Zostera marina) at high densities on a local scale. However, it is yet unknown if restored seagrass plants also lead to improved local biodiversity and ecosystem functioning in the intertidal zone. We therefore compared the macrozoobenthos communities of a small-scale restored meadow to 22 naturally occurring intertidal seagrass meadows. Using a taxonomic and trait-based approach we aimed to study 1) how intertidal seagrasses (Zostera marina and Zostera noltii) affect benthic communities and their functional trait distribution and 2) if a restored meadow facilitates benthic communities similar to natural meadows. We found that both natural and restored seagrasses increased abundances of benthic animals and the richness (both taxonomic and functional) of associated benthic communities compared to nearby unvegetated areas. Additionally, the presence of intertidal seagrass shifted benthic community composition both taxonomically and functionally, thus broadening the niche space for species inhabiting tidal flats. Seagrasses especially facilitated epifaunal species and traits associated with these animals. Surprisingly, our results indicate that the mere presence of seagrass aboveground structure is enough to facilitate benthic communities, as neither higher seagrass cover nor biomass increased benthic biodiversity in the intertidal zone. By studying the effect of seagrass restoration on benthic diversity, we found that the restored meadow functioned similarly to the natural meadows after only two years and that the success of our restoration efforts indeed led to local biodiversity enhancements. Our findings contribute to the understanding of the ecological functioning of intertidal seagrasses and can be used to define/refine conservation and restoration goals of these valuable ecosystems.